(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Numerical methods play a crucial role in approximating solutions to differential equations across various scientific and engineering disciplines where analytical solutions are elusive or impractical. This abstract explores advanced numerical techniques tailored for solving differential equations, focusing on their efficacy, accuracy, and computational efficiency. The finite element method (FEM) stands prominent among these methods, offering robust solutions for problems ranging from structural analysis to fluid dynamics. By discretizing the domain into finite elements, FEM transforms complex partial differential equations into algebraic equations, thus facilitating numerical approximation. Its versatility extends to nonlinear problems, adaptive mesh refinement, and parallel computing, enhancing scalability and performance. Another pivotal approach is the spectral method, leveraging orthogonal basis functions like Fourier or Chebyshev polynomials to achieve high-order accuracy. Spectral methods excel in problems with smooth solutions, exhibiting rapid convergence but demanding regularity in the solution domain. the finite volume method (FVM) emphasizes conserving quantities across discrete volumes, making it ideal for fluid flow simulations and transport phenomena. Its structured grid framework ensures robustness under complex geometries and unstructured grids, catering to diverse engineering applications. This research reviews these methods’ theoretical foundations, implementation challenges, and comparative advantages, emphasizing their applicability and limitations in practical scenarios. Understanding their computational intricacies and trade-offs aids researchers and practitioners in selecting the optimal numerical strategy for addressing specific differential equation problems.